Detection and Quantification of Stagonosporopsis cucurbitacearum in Seeds of Cucurbita maxima Using Droplet Digital Polymerase Chain Reaction - Murolo, Sergio; Moumni, Marwa; Mancini, Valeria; Allagui, Mohamed Bechir; Landi, Lucia; Romanazzi, Gianfranco (Frontiers in Microbiology, 2022)
Stagonosporopsis cucurbitacearum is an important seedborne pathogen of squash (Cucurbita maxima). The aim of our work was to develop a rapid and sensitive diagnostic tool for detection and quantification of S. cucurbitacearum in squash seed samples, to be compared with blotter analysis, that is the current official seed test. In blotter analysis, 29 of 31 seed samples were identified as infected, with contamination from 1.5% to 65.0%. A new set of primers (DB1F/R) was validated in silico and in conventional, real-time quantitative PCR (qPCR) and droplet digital (dd)PCR. The limit of detection of S. cucurbitacearum DNA for conventional PCR was 1.82 ×10-2 ng, with 17 of 19 seed samples positive. The limit of detection for ddPCR was 3.6 ×10-3 ng, which corresponded to 0.2 copies/µl. Detection carried out with artificial samples revealed no interference in the absolute quantification when the seed samples were diluted to 20 ng. All seed samples that showed S. cucurbitacearum contamination in the blotter analysis were highly correlated with the absolute quantification of S. cucurbitacearum DNA (copies/µl) in ddPCR (R2 = 0.986; p ≤0.01). Our ddPCR protocol provided rapid detection and absolute quantification of S. cucurbitacearum, providing offering a useful support to the standard procedure